2018
DOI: 10.1108/jkm-08-2017-0349
|View full text |Cite
|
Sign up to set email alerts
|

Internal and external search strategies of innovative firms: the role of the target market

Abstract: Purpose This paper aims to develop the concept of internal search of ideas to show the contrast between search strategies adopted by firms that introduce new products into local and international markets. Design/methodology/approach Based on data from 2,652 innovative firms, the paper uses factor analysis to explore and confirm appropriate groups of sources of innovative ideas. The analysis differentiates between internal and two types of external sources. Logistic and bivariate regressions reveal different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Technology-based collaboration networks are critical for improving firms' innovation outcomes (Goertzel et al, 2017;Najafi-Tavani et al, 2018). Through embedding in such networks, firms are able to access, search for and share relevant technological resources and information held by external partners (Ruiz-Pava and Forero-Pineda, 2018). The knowledge network can record the firms' knowledge combinatorial histories, in which the network structural characteristics of firms indicate their importance and knowledge combinatorial potential (Carnabuci and Bruggeman, 2009;Wang et al, 2014;Yayavaram and Ahuja, 2008).…”
Section: Collaboration Network and Knowledge Networkmentioning
confidence: 99%
“…Technology-based collaboration networks are critical for improving firms' innovation outcomes (Goertzel et al, 2017;Najafi-Tavani et al, 2018). Through embedding in such networks, firms are able to access, search for and share relevant technological resources and information held by external partners (Ruiz-Pava and Forero-Pineda, 2018). The knowledge network can record the firms' knowledge combinatorial histories, in which the network structural characteristics of firms indicate their importance and knowledge combinatorial potential (Carnabuci and Bruggeman, 2009;Wang et al, 2014;Yayavaram and Ahuja, 2008).…”
Section: Collaboration Network and Knowledge Networkmentioning
confidence: 99%
“…Existing research has found the relationship between boundary-spanning search and innovation, yet the results are still inconsistent. Some scholars argue that boundary-spanning search fosters innovation (Leiponen & Helfat, 2010;Ruiz-Pava & Forero-Pineda, 2018;Zhang, Li, & Zheng, 2017), whereas others suggest boundary-spanning search may have inverted U-shaped relationship with innovation (Ardito & Petruzzelli, 2017;Laursen & Salter, 2006;Zhang & Hu, 2017). In addition, boundary-spanning search may hamper innovation (Terjesen & Patel, 2017) or have no significant effect on innovation (Ferreras-Méndez, Fernández-Mesa, & Alegre, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This method was also chosen because there are two binary dependent variables with the same explanatory variables. The literature explains that the use of the bivariate probit model is an adequate method to perform regressions using two dependent variables (Criscuolo et al , 2018; Ruiz-Pava and Forero-Pineda, 2018).…”
Section: Methodsmentioning
confidence: 99%